Implementation of The 7th Batch of Teaching Campus Program in Improving Literacy and Numeracy Competencies of SMPN 1 Tuhemberua - Telaumbanua, Rolius; Zega, Riswan; Gea, Juni kristiani; Batee, Riang Rahmat Kristin (CV. Publikasi Indonesia, 2024)
The Kampus Mengajar program has become an important initiative to improve the quality of education in Indonesia. This study aims to determine the impact of the Kampus Mengajar Batch 7 program on the literacy and numeracy skills of 8th grade students at SMP Negeri 1 Tuhemberua, North Nias Regency. This study used an experimental method with a one-group pretest-posttest design. The 8th grade students consisted of 108 students, so the study population was all 8th grade students, while the sample was only 30 students. The researchers collected data using test techniques, then analyzed the data with descriptive statistics. The results showed that students' literacy and numeracy skills increased significantly after a series of Kampus Mengajar Batch 7 activities were carried out, where the average literacy score increased from 38.17 in the pretest to 55.83 in the posttest, and the numeracy score increased from 16.83 in the pretest to 64.17 in the posttest. This program also provides students with direct community service experience. However, collaboration between students and schools needs to be strengthened to ensure the sustainability of the program. Future research is expected to include more schools and more detailed factors to measure the success of this Teaching Campus program as a whole.